Avaliação emancipatória do currículo e desenvolvimento profissional : um estudo com formadores da licenciatura em Ciências Biológicas do IFRO - Sousa, Aparecida Gasguez de (2018)
This work is placed in the intersection of the fields of science education, educational evaluation, curriculum and teacher training, within the framework of paradigmatic changes and educational policies which have been implemented in Brazil and in a global context, affecting educational institutions at all levels, across the whole country. The general objective of the research was to analyze the contributions of the emancipatory evaluation process of the curriculum of the “licenciatura” [a graduation course with emphasis on teaching methods and pedagogy] in Biological Sciences offered by the Federal Institute of Education, Science and Technology (IFRO) – Colorado do Oeste campus for the professional development of the teachers of this course. The locus of the research is the Biological Sciences degree course of the, located in the rural area of the municipality of Colorado do Oeste, in the south of the state of Rondônia, Brazil. The method used was the collaborative research, which proposes intervention processes with the objective of emancipating the participants, making teachers and researchers more self-aware and activists about the educational setting in their workplaces. The research relied on the participation of 145 contributors, distributed as follows: 93 current students, 37 graduates and 15 teachers who work in the course. Students (93) and graduates (37) participated in the diagnostic research phase (institutional criticism) and contributed to the identification of the demands for the reformulation of the course curriculum.Several techniques were used for the production of the data: documentary research, online questionnaires for the graduates, instructional diagnosis, carried out through small groups formed by current students of the course, recording of interviews with teachers and participant observation during the meetings of the Núcleo Docente Estruturante ( NDE) [a group of professors in charge of the conception and consolidation of the pedagogical project of the course] and the collegiate of the course. We carried out an interpretative analysis of the data. The supported thesis is that, given the context of changes and uncertainties in educational policies, the emancipatory evaluation of the curriculum can contribute to the professional development of the teachers and of the institution. The results indicate that, in this type of evaluation research, the evaluation of higher education courses has been regulatory, but can become emancipatory, contributing to the professional development of teachers through autobiographical and collective reflection, with the development of the teaching identity. When that is carried out, the teacher ceases to be an object and becomes an agent; he or she becomes part of the investigative process, learning and transforming the educational context in which they operate. The existing curriculum, in its turn, can be developed through criticism and collective reconstruction of the political pedagogical project of the course. Such actions may be reflected in institutional development, with changes in existing norms, regulations and educational practices, making the educational process more democratic and participatory. It is concluded that collaborative research of an emancipatory nature can contribute to the professional development of teachers and of the institution.